A contingency model of the dominance route to influence in work teams: The moderating role of team competition - Gedik, Yeliz; Rink, Floor A.; Walter, Frank; Van der Vegt, Gerben S. (Sage Publications Ltd, 2023)
This paper presents a contingency model on the effectiveness of dominance as a route to influence in organizational work teams. In a field study (n = 397 members from 54 work teams), we observed that perceived intra-team competition represents a key context factor that moderates the relationship between dominance displays and influence attainment. Although dominant members attained more influence than non-dominant members, their influence was proportionally greater when team competition was high, rather than low. A follow-up scenario experiment (n = 429 participants) confirmed the proposed causal direction of this interaction effect. Moreover, this study showed that normative evaluations of (non-)dominant behavior drive the findings. Dominance displays were considered more appropriate, normal, and functional (i.e., normative) in teams with high competition, whereas non-dominant behavior was seen as more normative in teams where competition was low. Consequently, non-dominant members also gained influence in this last team situation, reducing the relative influence advantage of dominant members. The results support both the functional view and the contextual value perspective on hierarchy formation in teams, and inform organizations about how they can prevent dominance-based influence processes.
Keywords: dominance; influence; team competition; normative evaluations